Understanding wetland sub-surface hydrology using geologic and isotopic signatures - P. Sahu; P. K. Sikdar (Hydrology and Earth System Sciences, 2009)
This paper attempts to utilize hydrogeology and isotope composition of groundwater to understand the present hydrological processes prevalent in a freshwater wetland, source of wetland groundwater, surface water/groundwater interaction and mixing of groundwater of various depth zones in the aquifer. This study considers East Calcutta Wetlands (ECW) – a freshwater peri-urban inland wetland ecosystem located at the lower part of the deltaic alluvial plain of South Bengal Basin and east of Kolkata city. This wetland is well known over the world for its resource recovery systems, developed by local people through ages, using wastewater of the city. Geological investigations reveal that the sub-surface geology is completely blanketed by the Quaternary sediments comprising a succession of silty clay, sand of various grades and sand mixed with occasional gravels and thin intercalations of silty clay. At few places the top silty clay layer is absent due to scouring action of past channels. In these areas sand is present throughout the geological column and the areas are vulnerable to groundwater pollution. Groundwater mainly flows from east to west and is being over-extracted to the tune of 65×103 m3/day. δ18O and δD values of shallow and deep groundwater are similar indicating resemblance in hydrostratigraphy and climate of the recharge areas. Groundwater originates mainly from monsoonal rain with some evaporation prior to or during infiltration and partly from bottom of ponds, canals and infiltration of groundwater withdrawn for irrigation. Relatively high tritium content of the shallow groundwater indicates local recharge, while the deep groundwater with very low tritium is recharged mainly from distant areas. At places the deep aquifer has relatively high tritium, indicating mixing of groundwater of shallow and deep aquifers. Metals such as copper, lead, arsenic, cadmium, aluminium, nickel and chromium are also present in groundwater of various depths. Therefore, aquifers of wetland and surrounding urban areas which are heavily dependent on groundwater are vulnerable to pollution. In the area south of ECW isotope data indicates no interaction between shallow and deep aquifer and hence this area may be a better location to treat sewage water than within ECW. To reduce the threat of pollution in ECW's aquifer, surface water-groundwater interaction should be minimized by regulating tubewell operation time, introducing treated surface water supply system and artificial recharging of the aquifer.